Financial Incentives to Postpone Retirement and Further Effects on Employment - Evidence from a Natural Experiment - Barbara Hanel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
This paper examines the effect of the introduction of permanent benefit reductions for early retirees (i) on the duration until retirement entry and (ii) on the duration until exit from gainful employment. I estimate discrete time duration models using different error term specifications. Administrative data containing the full earnings history of the individuals are used. Since the reform implementing the benefit reductions was a natural experiment, a true causal effect can be identified. The permanent reduction of retirement benefit amounts causes a postponement of retirement entry by about fifteen months and a delay of employment exit by about nine months on average.
Keywords: H55; J26; 330; retirement insurance; labor force participation; natural experiment